Study of Structurally Induced Turbulence in Rotary Thermally Isolated Compressible Flow - Muhammad Zunair (00000203670); Dr Majid Ali (USPCAS-E, NUST, Islamabad, 2021)
TH-273
Keywords: MS-TEE Thesis MS Thesis